Numbers 5:11–31 as the Old Testament Background for Revelation 8:11 - Siemieniec, Tomasz (The Biblical Annals, 2024)
The article examines possible links between the ritual of bitter water, described in Numbers 5:11–31, and one of the aspects of the plague, described as the event following the third trumpet in the Book of Revelation (Rev 8:11). Such a connection has not been analysed by scholars so far. The ritual described in Numbers 5 not only has a legal meaning but it is also the starting point for a theological tradition of understanding adultery as a metaphor for Israel’s unfaithfulness to YHWH. The prophetic texts of the OT use motifs taken from Num 5 to depict the lawsuit that YHWH brings against the unfaithful people. According to the author of this article, the use of the motif of drinking bitter water in Rev 8:11 falls into a similar pattern. This is a ritual performed to reveal the guilt of the sinners described in Rev as hoi anthrōpoi.